Diagnosis of contralateral rare pulmonary cavity metastasis after lung squamous cell carcinoma surgery by electromagnetic navigation: one case report and review of the literature - Li, Zhengjun; Wang, Xiaoge; Liu, Chang; Ren, Yi (Frontiers in Medicine, 2024)
Background: lung cancer associated with cystic airspaces is a rare disease, and a rare imaging performance of non-small cell lung cancer. Due to the lack of conventional diagnosis methods, it is difficult to rely on imaging diagnosis. Therefore, the definitive diagnosis of these neoplastic lesions remains challenging.Case PresentationMethods:We summarize the follow-up and diagnosis of a rare cystic airspaces lung metastatic carcinoma in an elderly man with annular density shadow in the right inferior lobe 2 years after surgery for squamous cell carcinoma in the left inferior lobe.Results: During the follow-up of the patient, after the lesion of the lower lobe of the right lung was enlarged, the structural and imaging characteristics were identified, and a special method was selected, namely biopsy of the lesion under the electromagnetic navigation bronchoscope, for clear diagnosis and subsequent treatment. Conclusions:For pulmonary cystic airspaces,it is important to correctly identify their imaging features. Because of the possibility of malignancy，it is essential to stop the radiological study in time and to acquire the pathological diagnosis by an appropriate method.